Targeting the S1P/S1PR1 axis mitigates cancer-induced bone pain and neuroinflammation. Issue 9 (September 2017) - Grenald, Shaness A.; Doyle, Timothy M.; Zhang, Hong; Slosky, Lauren M.; Chen, Zhoumou; Largent-Milnes, Tally M.; Spiegel, Sarah; Vanderah, Todd W.; Salvemini, Daniela
Abstract : Abstract: Metastatic bone pain is the single most common form of cancer pain and persists as a result of peripheral and central inflammatory, as well as neuropathic mechanisms. Here, we provide the first characterization of sphingolipid metabolism alterations in the spinal cord occurring during cancer-induced bone pain (CIBP). Following femoral arthrotomy and syngenic tumor implantation in mice, ceramides decreased with corresponding increases in sphingosine and the bioactive sphingolipid metabolite, sphingosine 1-phosphate (S1P). Intriguingly, de novo sphingolipid biosynthesis was increased as shown by the elevations of dihydro-ceramides and dihydro-S1P. We next identified the S1P receptor subtype 1 (S1PR1) as a novel target for therapeutic intervention. Intrathecal or systemic administration of the competitive and functional S1PR1 antagonists, TASP0277308 and FTY720/Fingolimod, respectively, attenuated cancer-induced spontaneous flinching and guarding. Inhibiting CIBP by systemic delivery of FTY720 did not result in antinociceptive tolerance over 7 days. FTY720 administration enhanced IL-10 in the lumbar ipsilateral spinal cord of CIBP animals and intrathecal injection of an IL-10 neutralizing antibody mitigated the ability of systemic FTY720 to reverse CIBP. FTY720 treatment was not associated with alterations in bone metabolism in vivo. Studies here identify a novel mechanism to inhibit bone cancer pain by blocking the actions of the bioactive metabolites S1P and dihydro-S1P in lumbar spinal cord induced by bone cancer and support potential fast-track clinical application of the FDA-approved drug, FTY720, as a therapeutic avenue for CIBP. Abstract : Bone cancer induces bioactive metabolites S1P and dihydro-S1P production in lumbar spinal cord. Blocking S1P and dihydro-S1P actions through S1PR1 inhibits bone cancer pain.